FROST INVESTIGATION 1945-1946. REPORT ON WATERTOWN AIRFIELD, WATERTOWN, SOUTH DAKOTA FARGO MUNICIPAL AIRFIELD, FARGO NORTH DAKOTA AND GREAT BEND AIRFIELD, GREAT BEND, KANSAS. - ARCTIC CONSTRUCTION AND FROST EFFECTS LAB BOSTON MASS (1946)
This report presents the results of the frost investigations conducted at Watertown Airfield, Fargo Municipal Airfield, and Great Bend Airfield during the period November 1945 through May 1946. The investigations included the measurement of pavement heaving caused by frost action, the observation of subsurface temperatures, frost penetration and ground water table. The investigations include both flexible and rigid type pavements. Prepared in cooperation with Corps of Engineers, Omaha, Neb. Missouri River Div. Also includes Appendix 9. Aee also AD-712 357.